2017
DOI: 10.1016/j.cancergen.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific wild-type TP53 expression in the unaffected carrier parent of children with Li–Fraumeni syndrome

Abstract: Li-Fraumeni Syndrome (LFS) is an autosomal dominant disorder where an oncogenic TP53 germline mutation is passed from parent to child. p53 is a key tumor suppressor regulating cell cycle arrest in response to DNA damage. Paradoxically, some mutant TP53 carriers remain unaffected, while their children develop cancer within the first few years of life. To address this paradox, response to UV stress was compared in dermal fibroblasts (dFb) from an affected LFS patient vs. their unaffected carrier parent. UV induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(32 citation statements)
references
References 40 publications
(71 reference statements)
3
29
0
Order By: Relevance
“…The same considerations are applicable for nonsense mutations found in the TP53 gene. Many TP53 mutations have been reported as oncogenic drivers in a variety of malignancies, including breast, liver and brain 23‐30 . It is recorded in the ClinVar archive 31 that the TP53 mutations found in our patients, listed in Table 1, are known to be disease causing.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The same considerations are applicable for nonsense mutations found in the TP53 gene. Many TP53 mutations have been reported as oncogenic drivers in a variety of malignancies, including breast, liver and brain 23‐30 . It is recorded in the ClinVar archive 31 that the TP53 mutations found in our patients, listed in Table 1, are known to be disease causing.…”
Section: Discussionmentioning
confidence: 80%
“…as oncogenic drivers in a variety of malignancies, including breast, liver and brain. [23][24][25][26][27][28][29][30] It is recorded in the ClinVar archive 31 that the TP53 mutations found in our patients, listed in Table 1, are known to be disease causing.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies have shown that allele-specific mechanisms play a significant role in cancer development. At the germline variant level, several susceptibility variants identified by cancer GWA studies have been shown to have cis-regulatory effects for nearby genes, and there is evidence that this mechanism may also play a role in high-penetrance familial cancer syndromes [ 27 ]. At the somatic mutation level, a significant fraction of tumors have at least one somatically acquired-oncogenic mutation displaying allelic imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, allele-specific mechanisms have been speculated to play a role in modifying the penetrance of deleterious variants, for example in individuals with Li-Fraumeni syndrome, caused by germline damaging variation in the tumor suppressor gene TP53 [ 27 ]. Buzby et al reported a father-daughter duo where both were heterozygous carriers of a deleterious TP53 Ser241Tyr variant, but only the daughter developed tumors.…”
Section: Allele-specific Expression In Cancermentioning
confidence: 99%
“…Many of these studies have also focused on investigating these cellular responses to UV irradiation mediated by p53 and its mutants in vitro [ 13 , 14 , 15 , 16 , 17 ]. Hence, primary dermal fibroblast (dFb) cultures were established using tissue samples obtained from the affected LFS daughter and her unaffected father to begin comparing their in vitro responses to UV stress in our previous study [ 18 ]. It was hypothesized that the unaffected carrier father may counteract genotoxic stress by means more characteristic of homozygous wild-type TP53 individuals than that of his affected offspring.…”
Section: Introductionmentioning
confidence: 99%